Magnitude and financial implications of inappropriate diagnostic imaging for three common clinical conditions. (23rd January 2019) - Flaherty, Stephen; Zepeda, E David; Mortele, Koenraad; Young, Gary J
Abstract: Objective: To quantify the level of adherence to imaging guidelines for three common clinical indications for a commercially insured population. Design: Retrospective analysis of administrative claims data for commercially insured individuals with diagnostic imaging claims (MRI and X-ray) for either uncomplicated low back pain, non-traumatic knee pain or non-traumatic shoulder pain. Setting: The State of Massachusetts for 2010 and 2013. Participants: Adults with no chronic conditions and without evidence of prior management in the 12 months preceding to the initial office visit for each of the clinical indications. Main Outcomes Measures: Imaging procedures performed within 30 days of the initial office visit were classified as appropriate or inappropriate according to adherence to imaging guidelines from American College of Radiology. Results: More than 60% of lumbar spine MRI's were deemed inappropriate in 2010 and in 2013. Over 30% of MRI's for shoulder pain and knee pain were inappropriate in 2010 and in 2013. Patients age 18–59 with inappropriate imaging claims had significantly lower rates of surgical procedures within 90 days of imaging than those with appropriate imaging. Inappropriate imaging accounted for over 20% of annual imaging costs for the three clinical indications. Conclusions: Reducing inappropriate imaging procedures can lead to substantial savings through the elimination of unnecessary and low value procedures. Increased awareness of and adherence to best practice guidelines should be a focus of efforts to cut waste in our healthcare system.